2019
DOI: 10.1016/j.ydbio.2019.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Genetic markers enable the verification and manipulation of the dauer entry decision

Abstract: Phenotypic plasticity allows animals to survive in changing environments through the alteration of phenotypes or development. One of the best-studied examples of phenotypic plasticity is dauer larval development in the free-living roundworm Caenorhabditis elegans. When faced with hostile environments, C. elegans larvae can exit reproductive development and enter the stress-resistant and spore-like dauer larval stage. However, knowledge about how the dauer entry decision is made, and how the different tissues o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…Indeed, we found that the daf-15 mutants fail to display dauer-specific expression of lag-2p::gfp in the IL2 cell bodies (Fig 5H). This corresponds with a recent publication demonstrating reduction of dauer-specific expression of ets-10p::gfp in a daf-15 background [55]. To our surprise, the daf-15 partial dauer FLPs had extensive arborization (Fig 5G).…”
Section: Daf-16 Is Necessary For Il2 Arbor Formation During Dauer Busupporting
confidence: 92%
“…Indeed, we found that the daf-15 mutants fail to display dauer-specific expression of lag-2p::gfp in the IL2 cell bodies (Fig 5H). This corresponds with a recent publication demonstrating reduction of dauer-specific expression of ets-10p::gfp in a daf-15 background [55]. To our surprise, the daf-15 partial dauer FLPs had extensive arborization (Fig 5G).…”
Section: Daf-16 Is Necessary For Il2 Arbor Formation During Dauer Busupporting
confidence: 92%
“…Given the lack of dauer-specific features, we question whether these were true dauers. A recent publication showing reduction of dauer-entry expression of the ets-10p::gfp transgene in a daf-15 background (51). Additional experiments will be required to understand the possible interactions of DAF-18 and DAF-15 in IL2 arborization.…”
Section: Discussionmentioning
confidence: 99%
“…In light of the downregulation and redistribution of VGLU-2::GFP in dauers, it is notable that animals that enter the dauer arrest stage substantially remodel their cuticle and collagen composition (Cox et al 1981;Cox and Hirsh 1985;Kramer et al 1985;Lee et al 2017;Shih et al 2019). VGLU-2 expression changes may be required for these remodeling events.…”
Section: Discussionmentioning
confidence: 99%